Presence of Some Panallergens in Tomatoes from Organic and Classic Cultivations - Słownianek, Marta; Skorupa, Marta; Leszczyńska, Joanna (Lodz University of Technology Press, 2015)
Tomato (Lycopersicon esculentum Mill.) is probably the most commonly consumed vegetable worldwide. Although it contains a wide array of beneficial health nutrients and antioxidants, it may also cause adverse allergic reactions in sensitized people. Tomato allergy affects from 1.5% to 16% of the population with food allergy and is often accompanied by allergy to pollen and latex [1]. The aim of the study was to investigate the relation between method of tomato cultivation and allergens’ content in different tomato varieties.